THE EFFECT OF STORY MAPPING STRATEGY ON STUDENTS’ ACHIEVEMENT IN WRITING NARRATIVE TEXT - Roniko Ilham Lubis (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: The objective of this research is to know whether there is a significant effect of story mapping strategy on students’ writing narrative text achievement at the tenth grade students of MAN Panyabungan. This research uses experimental method with the experimental research design; one group pre-test and post-test design. The population is all of the tenth grade students which consist of 264 students. Technique sampling that used on this research is purposive sampling and the number of the sample consists of 38 students. In collecting the data, the researcher uses observation sheet to get the data of the application of story mapping strategy and test to get the data of the students’ writing narrative text achievement. The researcher uses statistic process in analyzing by using t test formula. Based on the data that has been analyzed, the result of analyzed data showed that t count is higher than t table (t count 13.37 > t table 2.03), and the hypothesis is accepted. It means that there is a significant effect of story mapping strategy on students’ writing narrative text achievement at the tenth grade students of MAN Panyabungan. Keywords: story mapping strategy, writing skill, narrative text. Abstrak: Tujuan penelitian ini adalah untuk mengetahui apakah ada sebuah pengaruh yang signifikan dari strategi story mapping terhadap pencapaian siswa dalam menulis teks naratif di kelas sepuluh MAN Panyabunagn. Penelitian ini menggunakan metode eksperimental dengan rancangan penelitian experimental; one group pre-test post-test design. Populasi penelitian terdiri dari 264 siswa kelas sepuluh. Teknik penarikan sampel yang digunakan dalam penelitian ini adalah penarikan sampel sistematis sederhana dan jumlah sample terdiri dari 38 siswa. Dalam pengumpulan data, peneliti menggunakan lembar observasi untuk menjaring data dari pengaplikasian strategi story mapping dan tes untuk menjaring data mengenai pencapaian siswa dalam menulis teks naratif. Peneliti menggunakan proses statistic dalam analisis data, yaitu rumus tes t. Berdasarkan data yang telah di analisis, hasil analisis data menunjukkan bahwa t hitung lebih besar dari pada t table (t hitung 13.37 > t table 2.03), dan, hipotesis diterima. Hal ini berarti ada sebuah pengaruh yang signifikan dari strategi story mapping terhadap pencapaian siswa dalam menulis teks narasi di kelas sepuluh MAN Panyabungan. Kata kunci: strategi story mapping, kemampuan menulis, teks naratif.